2017
DOI: 10.1159/000484719
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenosis Contralateral to Acute Tandem Occlusion: An Independent Predictor of Poor Clinical Outcome after Mechanical Thrombectomy with Concomitant Carotid Artery Stenting

Abstract: Background and Purpose: Cerebral ischemic strokes due to extra-/intracranial tandem occlusions (TO) of the anterior circulation are responsible for causing mechanical thrombectomy (MT). The impact of concomitant contralateral carotid stenosis (CCS) upon outcome remains unclear in this stroke subtype. Methods: Retrospective analysis of prospectively collected data of 4 international stroke centers between 2011 and 2017. One hundred ninety-seven consecutive patients with anterior TO were treated with MT and acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…Based on our current analysis, we suggest that patients suffering from acute TO should not be deprived of acute CAS. Reasons for this might be that (i) the vulnerable carotid lesion is stabilized, which prevents further cerebral thromboembolism within the post-interventional period, and (ii) the occurrence of sICH in acute TO seems justifiable with a rate between 5 and 11%, as demonstrated in large studies [7,8,23,[35][36][37]. Furthermore, the recent sub-analysis of the ESCAPE trial demonstrated that TO patients undergoing acute carotid intervention tended to have a better clinical outcome compared to staged treatment or medical therapy alone (65 vs. 54%) [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our current analysis, we suggest that patients suffering from acute TO should not be deprived of acute CAS. Reasons for this might be that (i) the vulnerable carotid lesion is stabilized, which prevents further cerebral thromboembolism within the post-interventional period, and (ii) the occurrence of sICH in acute TO seems justifiable with a rate between 5 and 11%, as demonstrated in large studies [7,8,23,[35][36][37]. Furthermore, the recent sub-analysis of the ESCAPE trial demonstrated that TO patients undergoing acute carotid intervention tended to have a better clinical outcome compared to staged treatment or medical therapy alone (65 vs. 54%) [5].…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in accordance with the Declaration of Helsinki. Clinical data of some of the patients have been published in previous studies in a different context [7,8].…”
Section: Study Design and Clinical Assessmentmentioning
confidence: 99%
“…All patients treated due to isolated occlusion of anterior cerebral artery and with an unknown onset of symptoms were excluded. Patients treated with MT and acute carotid artery stenting due to tandem occlusions were excluded as this cohort was analyzed in a prior study ( 10 ). According to neurological guidelines, patients received IVT whenever possible.…”
Section: Methodsmentioning
confidence: 99%
“…In case of a horizontal or tortuous course of the vessel or a very short stenosis, maximum intensity projections and reconstructions were consulted ( 19 ). A luminal stenosis of >50% was defined as a relevant CCAS ( 10 ). The amount of contrast agent was 1.2–1.5 mL/kg body mass and minimum flow rate was 4.5 mL/s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation